2013
DOI: 10.1080/15287394.2013.798846
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide Contamination Reduces Beneficial Fungi in Bee Bread Based on an Area-Wide Field Study in Honey Bee,Apis mellifera, Colonies

Abstract: Fermentation by fungi converts stored pollen into bee bread that is fed to honey bee larvae, Apis mellifera, so the diversity of fungi in bee bread may be related to its food value. To explore the relationship between fungicide exposure and bee bread fungi, samples of bee bread collected from bee colonies pollinating orchards from 7 locations over 2 years were analyzed for fungicide residues and fungus composition. There were detectable levels of fungicides from regions that were sprayed before bloom. An organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 17 publications
1
58
1
3
Order By: Relevance
“…Conversely, bees foraging in landscapes dominated by agricultural areas where pesticides are applied, will have higher exposure risk even for pollinators surveyed in orchards with low PUI [62]. Interactions between pesticide regime and landscape have been observed previously by comparing bee diversity in organic versus conventional fields, with benefits of organic farming detected only in agriculturally intensified landscapes [70].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Conversely, bees foraging in landscapes dominated by agricultural areas where pesticides are applied, will have higher exposure risk even for pollinators surveyed in orchards with low PUI [62]. Interactions between pesticide regime and landscape have been observed previously by comparing bee diversity in organic versus conventional fields, with benefits of organic farming detected only in agriculturally intensified landscapes [70].…”
Section: Discussionmentioning
confidence: 94%
“…Altered foraging efficiency or nest recognition could decrease offspring production, but so could increased susceptibility of larvae to pesticides if toxins made it into pollen provisions. Honeybee pollen collected from orchards sprayed with fungicides had fewer beneficial fungal species [62], indicating that digestion of pollen masses by larvae may be altered by fungicide exposure if such mutualisms are important for non-Apis nutrition, as well. At present, most laboratory toxicity tests are conducted on eusocial Apis and Bombus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have already shown the possible modification of microbial composition both at beebread level [62], [72] and at intestinal level [73]. This modification in the composition of microbiota may lead to dysbiosis [74].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these molecules are suspected to cause important problems at very low doses and may contribute to bees' death [12]. Another molecule, boscalid, which is a fungicide of the carboxamide family, may be involved in these disorders [41]. Thus, the study of fungicides in beehive matrices is of growing interest to beekeepers and ecotoxicologists.…”
Section: Introductionmentioning
confidence: 98%